Struggling to achieve desired results from your AR projects? Insights from the Evaluative Study of Action Research may help. Issue 5 (20th October 2019) - Robinson, Fiona; Piggot Irvine, Eileen; Youngs, Howard; Cady, Phil
ABSTRACT: The aim of this paper is to share the results of a global inquiry into the outcomes and impacts of action research (AR) projects. This is one of a series of papers associated with the Evaluative Study of Action Research (ESAR), an initiative launched by an international team of seven action researchers, to understand if the espoused intents articulated in AR projects are realized and why certain project inputs and processes may result in more effective outputs and outcomes than others. After identifying nearly 500 global AR projects through a snowball sampling methodology, a mixed methods approach was used to distribute a survey of Likert-scale and open-ended questions to project leads. In total, 195 projects were approved for inclusion in the ESAR global AR directory and 174 participants completed the related short survey. A key finding of our study was that the majority of global projects (85.7%) resulted in changes in outcomes. Furthermore, there was no particular combination of inputs, or implementation tactic, to predictably create such change. Our research supports the use of AR as a methodology to identify and achieve espoused change among groups while remaining adaptive to embrace the nuances of unpredictable, contextual and culturally specific situations.